Corrections to “Development p, q, r−Spherical Fuzzy Einstein Aggregation Operators: Application in Decision-Making in Logo Design” - Lin Kang; Salma Khan; Muhammad Rahim; Kamal Shah; Thabet Abdeljawad (IEEE Access)
In the above article [1], reference 48 was retracted. As the work in this reference is no longer reliable, we are removing it from the reference list AND replacing it with [2]. The corresponding discussion in Section V-F. Table 10 is changed to the following:TABLE 10Comparison MethodsScore valuesOption $Δ _{1}$ $Δ _{2}$ $Δ _{3}$ $Δ _{4}$ $Δ _{5}$ Garg et al. [47]0.23490.18640.17900.15480.1945 $Δ _{1}$ Mahmood et al. [2]0.15170.12090.10510.09450.1384 $Δ _{1}$ Mahnaz et al. [49]0.27630.23550.22780.20310.2534 $Δ _{1}$ Rahim et al. [25]0.54820.51470.50380.49700.5326 $Δ _{1}$ Akhtar et al. [50]0.43550.38480.37160.34180.4093 $Δ _{1}$ Ashraf et al. [51]0.31470.25600.24810.23570.2839 $Δ _{1}$ Ashraf et al. [52]0.49120.45440.43560.42650.4873 $Δ _{1}$